Інтеграція видів діяльності у процесі проходження студентами педагогічної практики - Тимчик, Олеся; Полковенко, Ольга (Educological discourse, 2013)
The article highlights the importance of integration of different types of activities in the process of teaching practice of prospective primary school teachers. The author analyses the techniques of integration and prerequisites which provide the integrated approach to students’ professional activities.